Suppressed HF Behaviour in the Periodic Anderson Model - I. S., Okunzuwa; Ejere, Arthur I. I. (European Scientific Journal, ESJ, 2018)
The periodic Anderson model is applied to 4 electrons on 4 sites with periodic boundary conditions. We applied magnetic field to the localized forbitals, EÏƒf. The number of electrons is taken to be one per site and the interactions between different sites is restricted to nearest neighbors. The many body eigenvalues are calculated exactly using exact diagonalization technique. We find that the specific heat is suppressed by the variation of the band energy of the localized f-orbitals as mediated by the application of the magnetic field, H, under various hybridization energy. A continuous suppression of the specific heat reduces the heavy fermion behavior in the system.